1935
DOI: 10.1084/jem.61.5.593
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Leukosis to Sarcoma of Chickens

Abstract: A transmissible strain of sarcoma (Strain 13) is described that took its origin in a chicken inoculated with leukosis of Strain 1. The virus of Strain 13 produces sarcoma in the breast muscle injected with it and after intravenous inoculation it produces diffuse sarcomatosis of the spleen, bone marrow, and several other organs. The available evidence suggests that Strain 13 is caused by a single virus with ability to produce diffuse endothelial growth in the blood-forming organs associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1936
1936
1999
1999

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The virus of Strain 11 has distinctive features t h a t differ from those of the three other sarcomata observed b y us (3,4), but is similar to the spindle cell sarcoma of Rous (2, 1). All chickens inoculated with it were kept in one room, often in one cage, together with chickens inoculated with our different agents of leukosis and sarcoma.…”
Section: Characteristics Of Strain 11mentioning
confidence: 72%
See 2 more Smart Citations
“…The virus of Strain 11 has distinctive features t h a t differ from those of the three other sarcomata observed b y us (3,4), but is similar to the spindle cell sarcoma of Rous (2, 1). All chickens inoculated with it were kept in one room, often in one cage, together with chickens inoculated with our different agents of leukosis and sarcoma.…”
Section: Characteristics Of Strain 11mentioning
confidence: 72%
“…Such strains have been recently described b y several workers (6,7,4) and the question arose whether they are produced b y one or Several viruses. In Experiments A and B the virus of pure sarcoma (Strain 11) and the virus of pure leukosis (Strain 1) were injected separately into the same chickens.…”
Section: Combined Inoculation With a Pure Leukosis And A Pure Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…The Sea receptor was identified as the cellular homologue of the avian retroviral oncoprotein v-Sea. This avian erythroblastosis virus (S13) induced sarcomas, erythroblastosis, and anemia in infected birds (11,12). Transformation of erythroid cells with the sea onco- gene rendered them erythropoietin independent (13,14).…”
Section: Table II Edman Sequencing Of Chicken Serum Mspmentioning
confidence: 99%
“…In this report we describe the isolation of another member of this gene family, the sea gene of the S13 avian erythroblastosis retrovirus. The S13 virus causes sarcomas, erythroblastosis, and anemias on injection into young chicks (7). Recent characterization of this virus revealed that its genome length was 8.5 kilobases (kb), and this virus encoded normal-sized gag and gag-pol products but an abnormally sized env glycoprotein of 155 kDa, gp155 (8)(9)(10).…”
mentioning
confidence: 99%